Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Taman Wisata Pendidikan Purbasari Pancuran Mas Purbalingga - Amel Dea Fenansa; Ratna Puji Astuti; Herwiek Diyah Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this research is to determine and analyze the significance of the influence of communication, work discipline, organizational culture and compensation on employee performance at the Purbasari Pancuran Mas Purbalingga Educational Tourism Park. This type of research is quantitative, with a population of 100 employees. The sampling technique for this research used proportionate stratified random sampling to obtain a sample of 85 respondents. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, F test and t test. The analysis tool used is the SPSS statistical data processing application. The results of the research show that the variables of communication, work discipline, organizational culture and compensation have a positive and significant influence on the performance of employees at the Purbasari Pancuran Mas Purbalingga Educational Tourism Park. Based on the coefficient of determination of communication variables, work discipline, organizational culture and compensation have an influence of 61.20% on employee performance variables, while the remaining 38.80% is influenced by other variables. The implication of this research is that in an effort to continue to improve employee performance, management needs to implement appropriate policies in a way that maintains the communication process every day, increases employee work effectiveness, increases employee self-confidence and pays attention to the amount of incentives in accordance with work performance.